EFEKTIVITAS EDUKASI DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN IBU HAMIL TENTANG PEMERIKSAAN ANTENATAL CARE (ANC) DI KELURAHAN SEBERANG TEMBILAHAN BARAT WILAYAH KERJA PUSKESMAS TEMBILAHAN KOTA - Widya Eka Putri; Rifa Yanti; Fajar Sari Tanberika; Komaria Susanti (STIKES HUSADA GEMILANG, 2026)
One way to increase maternal motivation regarding ANC examinations during pregnancy is by educating mothers using booklet media. Media in health education can be interpreted as a tool for health promotion to facilitate communication and dissemination of information. ANC coverage at the Tembilahan Kota Health Center each year never reaches the target. This is because pregnant women do not undergo examinations at health facilities. The aim of the research is to determine the application of education using booklet media to the knowledge of pregnant women regarding Antenatal Care (ANC) examinations. This type of research is quantitative and pre-experimental design, one group design with pretest-posttest. This research was conducted at the Tembilahan Kota Community Health Center, Indragiri Hilir Regency in 2026. The population was pregnant women and a sample of 15 people, with. total sampling. The research instruments were questionnaires and booklets. The univariate results showed that the average knowledge of mothers about Antenatal Care before being given education using booklets was 56.00 with the lowest knowledge value being 20 and the highest knowledge value being 90 and after being given education using booklets it increased to 79.33 with the lowest knowledge value being 50 and the highest value reaching 100. Bivariate results using the paired sample test obtained p-value = 0.000 < 0.05, the research conclusion was that there was an influence of education using audio-visual media on mothers' knowledge about Antenatal Care. It is hoped that the Community Health Center will be more innovative in providing educational media for the community, especially pregnant women, about nutritional health problems during pregnancy. One way to increase maternal motivation regarding ANC examinations during pregnancy is by educating mothers using booklet media. Media in health education can be interpreted as a tool for health promotion to facilitate communication and dissemination of information. ANC coverage at the Tembilahan Kota Health Center each year never reaches the target. This is because pregnant women do not undergo examinations at health facilities. The aim of the research is to determine the application of education using booklet media to the knowledge of pregnant women regarding Antenatal Care (ANC) examinations. This type of research is quantitative and pre-experimental design, one group design with pretest-posttest. This research was conducted at the Tembilahan Kota Community Health Center, Indragiri Hilir Regency in 2026. The population was pregnant women and a sample of 15 people, with. total sampling. The research instruments were questionnaires and booklets. The univariate results showed that the average knowledge of mothers about Antenatal Care before being given education using booklets was 56.00 with the lowest knowledge value being 20 and the highest knowledge value being 90 and after being given education using booklets it increased to 79.33 with the lowest knowledge value being 50 and the highest value reaching 100. Bivariate results using the paired sample test obtained p-value = 0.000 < 0.05, the research conclusion was that there was an influence of education using audio-visual media on mothers' knowledge about Antenatal Care. It is hoped that the Community Health Center will be more innovative in providing educational media for the community, especially pregnant women, about nutritional health problems during pregnancy.